e-Consistent Equilibrium - Ehud Lehrer; Sylvain Sorin (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
We deal with the concept of e-consistent equilibrium which corresponds to strategies inducing an e-equilbrium in any subgame reached along the play path. Examples and existence conditions are given.
Keywords: 330